Celebrating Forty Years of Politique africaine: Interview with Sandrine Perrot - (:unkn) unknown (My University, 2021)
Politique africaine is a French journal of African studies, first published in 1981. Published by Karthala, Politique africaine is a multidisciplinary peer review journal centred on the analysis of politics in Africa. Founded as a clear departure from conventional approaches on Africa, it has emerged, in France and abroad, as a reference publication. This year, the journal celebrates 40 years of existence and 162 issues. Interview with Sandrine Perrot, a long-standing member of the journal and Director of the publication. Interview by Miriam Périer. English version by Miriam Périer and Caitlin Gordon Walker
Keywords: African Research